Pros and Cons of Prostate Cancer Screening: Associations With Screening Knowledge and Attitudes Among Urban African American Men - Davis, Stacy N.; Diefenbach, Michael A.; Valdimarsdottir, Heiddis; Chen, Tianle; Hall, Simon J.; Thompson, Hayley S. (Journal of the National Medical Association, 2010)
Discussion of the pros and cons of prostate cancer screening tests, rather than routine screening, is recommended to support informed screening decisions, particularly among African American men. This study explored physician explanation of pros and cons of the prostate-specific antigen (PSA) test and digital rectal exam (DRE) and its association with knowledge and screening attitudes. Two hundred-one African American men were asked if a physician had ever provided a comprehensive explanation of pros and cons of the PSA test and DRE. All men completed a 10-item prostate cancer knowledge scale and a subset completed a 26-item attitudes measure. Only 13% of the sample reported receiving a comprehensive explanation. Also, prostate cancer knowledge in the sample was low (mean = 43% correct). Multivariate analyses revealed that total prostate cancer knowledge was associated with men receiving a comprehensive explanation (p = .05), as well as past prostate cancer screening (p = .02) and younger age (p = .009). Although comprehensive explanation of prostate cancer screening was related to total prostate cancer knowledge, it was unrelated to a subset of items that may be central to fully informed screening decisions. Furthermore, comprehensive explanation of prostate cancer screening (p = .02), along with DRE recommendation (p = .009) and older age (p = .02), were related to fewer negative screening attitudes. Findings suggest that continued focus on patient education and physician communication is warranted.